Discussion on LNG Cold Energy Utilization Methods - Liu, Yuanjie; Zhang, Yuxin; Zhang, Xinhai; Li, Tong (International Journal of Natural Resources and Environmental Studies, 2024)
Natural gas is known as a clean energy source due to its environmental benefits and economic viability, widely used in both industrial and residential sectors. Liquefied natural gas (LNG) is characterized by its small volume and low-cost transportation over long distances (by ship), with about 25% of international trade conducted using LNG. In recent years, China’s LNG supply has been steadily increasing, and it is expected that by 2040, China’s demand for LNG will exceed 15% of the global total. LNG is a low-temperature (−162°C) liquid mixture formed by purifying natural gas to remove acids and water, followed by low-temperature condensation. LNG receiving stations typically use seawater heating to vaporize LNG into gaseous natural gas for export, with the large amount of cold energy released during vaporization absorbed by seawater and discharged into the ocean, approximately 830 kWh/kg. Based on China’s receiving capacity in 2018, the cold energy from LNG was equivalent to 2.07 billion kWh, and it is projected to reach 5.98 billion kWh by 2023, indicating a rich resource of cold energy. As China imports significant amounts of LNG, the comprehensive utilization of LNG cold energy becomes increasingly important.